Designing Uniformly Layered FeTiO3 Assemblies Consisting of Fine Nanoparticles Enabling High-Performance Quasi-Solid-State Sodium-Ion Capacitors - Liu, Lei; Zhao, Zhongchen; Hu, Zhengqiang; Lu, Xiangjun; Zhang, Shijia; Huang, Ling; Zheng, Yi; Li, Hongsen (Frontiers in Chemistry, 2020)
Sodium-ion capacitors (NICs) that integrated the dual advantages of high output of supercapacitors and high energy density of batteries have stimulated growing attention for next generation of practical electrochemical energy storage devices. The last years have witnessed the unprecedentedly rapid emergence of ilmenite materials, which presents great promise in realm of energy storage. However, NICs based on ilmenite materials are scarcely demonstrated by far. Besides, most of the current devices explored applied the flammable liquid electrolytes, leading to a concern about unexpected leakage and potential safety problems. Herein, a quasi-solid-state NIC is constructed by employing the prepared uniformly layered FeTiO3 assemblies consisting of fine nanoparticles as anode and sodium ion conducting gel polymer as electrolyte. The resulting device delivers a high-energy-high-power density (79.8 Wh kg-1, 6750 W kg-1), which is among the state-of-the-art NICs. Furthermore, the assembled quasi-solid-state device also manifests long-term cycling stability over 2000 cycles with capacity retention ~80%. The uniformly layered FeTiO3 assemblies have great potential in developing low-cost and high-performance electrode for next generation sodium and other metal ions-based energy storage devices.